2021
DOI: 10.37360/blacpma.21.20.5.34
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as an anti-asthmatic agent: could this stilbenoid help against COVID-19 in any way? A meta-analysis

Abstract: Resveratrol is a phenolic phytoconstituent found in many plants. This molecule has always caught the attention of scientists because of biological potentials such as inhibition of inflammation, oxidative stress and platelet aggregation as well as to prevent/protect against cardiovascular and neurodegenerative disease/disorders. Literature search have been conducted over resveratrol in covid-19 and asthma studies published in Pubmed and Google Scholars until 30 September 2020. The criteria used in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…In a recent meta‐analysis, resveratrol effectively lowers cytokine storms and inflammation in coronavirus disease‐19 (COVID‐19). Additionally, it modulates the pathways involved in antiviral defense (Parlar et al, 2021). The preclinical data of resveratrol highlights its role as an immunomodulator, but more clinical trials must be conducted to confirm its potential.…”
Section: Immunomodulator Activity Of Several Phytoconstituentsmentioning
confidence: 99%
“…In a recent meta‐analysis, resveratrol effectively lowers cytokine storms and inflammation in coronavirus disease‐19 (COVID‐19). Additionally, it modulates the pathways involved in antiviral defense (Parlar et al, 2021). The preclinical data of resveratrol highlights its role as an immunomodulator, but more clinical trials must be conducted to confirm its potential.…”
Section: Immunomodulator Activity Of Several Phytoconstituentsmentioning
confidence: 99%
“…Resveratrol has been tested in clinical trials for patients with type 2 diabetes, nonalcoholic fatty liver syndrome, or polycystic ovary syndrome by modulating the expression of transcription factors and cytokines in circulating immune cells. 83,84 Additionally, a recent meta-analysis concluded that resveratrol treatment effectively reduces inflammation and cytokine storms as well as regulates pathways involved in antiviral defense in COVID-19 patients 85.…”
mentioning
confidence: 99%